Evaluasi Sistem Penambangan Coking Coal untuk mencapai nilai Crucible Swelling Number (CSN) 3-7 di Pit Haju PT Pamapersada Nusantara Jobsite Adaro Met Coal di Kalimantan Tengah - Fariz Aditya; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2018)
PT Pamapersada Nusantara Jobsite Adaro Met Coal is one of the company's pilot projects in world-class coking coal mining. The right technology and coking coal mining system must be implemented because the quality produced greatly affects the customer's trust. Coking coal is a type of coal that is used as a fuel as well as a reducing agent in the iron / steel industry. One important indicator in distinguishing the quality of coking coal with thermal coal types is the CSN (Crucible Swelling Number) test. Coking coal must have a CSN value of at least 3. Coking coal can decrease in quality due to contamination during the mining process. Based on problem analysis there are 3 mining activities that can affect the quality of coking coal, namely: front loading preparation activities, loading and hauling activities and coal accumulation activities in ROM stock. After applicated improvement of  the mining system in each of these activities comprehensively and then pouring it into the SOP design for coking coal mining, the CSN value was increased by 66% and the ash value decreased by 43%.Keywords: Preparation Front Loading, Loading and Hauling Activities, Coal Accumalation Activities, CSN and Ash